Genes of the Escherichia coli pur regulon are negatively controlled by a repressor-operator interaction. - He, B (1990)
Fusions of lacZ were constructed to genes in each of the loci involved in de novo synthesis of IMP. The expression of each pur-lacZ fusion was determined in isogenic purR and purR+ strains. These measurements indicated 5- to 17-fold coregulation of genes purF, purHD, purC, purMN, purL, and purEK and thus confirm the existence of a pur regulon. Gene purB, which encodes an enzyme involved in synthesis of IMP and in the AMP branch of the pathway, was not regulated by purR. Each locus of the pur regulon contains a 16-base-pair conserved operator sequence that overlaps with the promoter. The purR product, purine repressor, was shown to bind specifically to each operator. Thus, binding of repressor to each operator of pur regulon genes negatively coregulates expression.